Home » Aptitude » Algebra » Question
  1. The simplified value of 1 -
    2xy
    ÷
    x3 - y3
    - 3xy is
    x2 + y2x - y

    1. 1
      x2 - y2

    2. 1
      x2 + y2

    3. 1
      x - y

    4. 1
      x + y
Correct Option: B

Expression = 1 -
2xy
÷
x3 - y3
- 3xy
x2 + y2x - y

Expression =
x2 + y2 - 2xy
÷
(x - y)(x2 + xy + y2)
- 3xy
x2 + y2x - y

Expression =
(x - y)2
÷ (x2 + xy + y2 - 3xy)
x2 + y2

Expression =
(x - y)2
÷ (x2 - 2xy + y2)
x2 + y2

Expression =
(x - y)2
÷ (x - y)2
x2 + y2

Expression =
1
x2 + y2



Your comments will be displayed only after manual approval.